E Efektivitas Metode Focus Group Discussion (FGD) Menggunakan Media Reminder Medication Card Terhadap Kepatuhan Ibu Hamil Dalam Mengkonsumsi Tablet Tambah Darah di Puskesmas Pelambuan - Wardhani, Yuliana; Saputri, Rina; Hateriah, Siti (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: Unadheence to taking blood supplements in pregnancy was still high. Health education with focus group discussion (FGD) method and reminder medication card media expected to increasing the adherence of consuming blood supplements regularly. Objective: To analyze the effectiveness of focus group discussion (FGD) using reminder medication card to pregnant women adherence on comsuming blood supplement tablet in Pelambuan Health Care Center. Methods: This true experimental pretest-posttest control group research conducted to 64 pregnant women on intervension and control group with simple random sampling technique on June at Pelambuan Health Care Center and analyzed with Wilcoxon and Mann Whitney U Test. Results: About 65,6% of intervension group were unadherence and 81,3% on control group were unadherence in pretest. About 90,6% of intervension group were adherence and 75% on control group were unadherence in posttest. There is a difference of pretest and posttest result on intervension group (p value = 0,000) and no difference on control group (p value = 0,317). There is a difference between intervension and control group (p value = 0,000). Conclusion: Focus group discussion (FGD) using reminder medication card effective to increasing pregnant women’s adherence on comsuming blood supplement tablet in Pelambuan Health Care Center.